Determining the origin and changing shape of landscape‐scale rock formations with three‐dimensional modelling: The Borologa rock shelters, Kimberley region, Australia. Issue 4 (2nd May 2021) - Genuite, Kim; Delannoy, Jean‐Jacques; David, Bruno; Unghango, Augustine; Corporation, Balanggarra Aboriginal; Cazes, Gaël; Fulop, Reka; Fink, David; Codilean, Alexandru; Ouzman, Sven; Veth, Peter; Harper, Sam; et al.
Abstract: Archaeologists often wonder how and when rock shelters formed, yet their origins and antiquity are almost never systematically investigated. Here we present a new method to determine how and when individual boulders and rock shelters came to lie in their present landscape settings. We do so through 3D laser (LiDAR) mapping, illustrating the method by example of the Borologa Aboriginal site complex in the Kimberley region of northwestern Australia. Through a combination of geomorphological study and high‐resolution 3D modelling, individual blocks of rock are refitted and repositioned t680their originating cliff‐line. Preliminary cosmogenic nuclide ages on exposed vertical cliff faces and associated detached boulders above the Borologa archaeological sites signal very slow detachment rates for the mass movements of large blocks down the Drysdale Valley slopes, suggesting relative landscape stability over hundreds of thousands of years (predating the arrival of people). These findings offer hitherto unknown details of the pace of regional landscape evolution and move us toward a better understanding of patterns of human occupation in a context of relatively stable rock outcrops both within the sites and across the region.